The Effect of Working Capital, Liquidity and Solvency on Profitability at PT Nippon Indosari Corpindo, Tbk - Eni Puji Astuti (Jurnal Ad'ministrare, 2020)
The main attraction for owners of company shareholders lies in the profitability ratio that shows the results of the management of the company's management of the funds invested. This study aims to determine: The Effect of Working Capital, Liquidity and Solvency on the Profitability of PT. Nippon Indosari Corpindo Tbk, both partially and simultaneously. Descriptive quantitative research methods, the data used are secondary data in the form of financial statements of PT. Nippon Indosari Corpindo Tbk, for a period of 9 years from 20010 - 2018 obtained through the IDX (Indonesia Stock Exchange). The analytical method used is the classic assumption test, multiple linear regression analysis, coefficient of determination and hypothesis testing. Based on the analysis results obtained the coefficient of determination (R2) of 0.928 or equal to 92.8%, which means that the contribution made by working capital, liquidity and solvency to profitability reaches 92.8.3% the remaining 7.2% is influenced by other variables which is not researched. Based on the t test partially working capital on profitability there is an effect where tcount -5.847> t table 2.575 and significance value 0.02 <0.05 and partially liquidity on profitability has no effect where tcount 1.846 <t table 2.575 and significance value 0.124> 0.05 and partially solvency to profitability there is the influence of tcount -3.386> ttable 2.575 and significance value 0.02 <0.05 based on the f test simultaneously working capital, liquidity and solvency affect the profitability where Fcount 21.477> Ftable 5.41 with a significant value of 0.003 <0.05